Encyclopedia of animal science - Baer, Charlotte Kirk; Pond, Wilson G. , 1930-; Ullrey, Duane E. (CRC Press, 2011)
"Written and edited by a distinguished team of experts, this encyclopedia encompasses animal physiology; animal growth and development; animal behavior; animal reproduction and breeding; alternative approaches to animal maintenance; meat science and muscle biology; farmed animal welfare and bioethics; and food safety. Organized with reader-friendly descriptions of technologies, the second edition consists of more than 300 entries--many of which are new--ranging from adaptation and stress, to zoos and aquariums. With 2500 references and hundreds of figures, equations, and tables, it covers new developments in genomics, transgenesis, cloning, and mathematical model constructions"